Teachers' perceptions of and practices in teachers' quality circles in selected public schools - Sapit, Grace Baclayon
This research study sought to determine the status of development of Teachers’ Quality Circles (TQC) in Marikina District 2 public high schools based on the perceptions of teachers. The study is timely in that after two years of implementation of the TQCs, it provides a seminal work on which to build further research. The TQC is based on the professional learning communities (PLC), which have been used in other countries with some success. The research study used a mixed methods convergent parallel model design with survey and group interviews as data collection methods. The survey questionnaire used the five dimensions of a professional learning community as rated by teachers, employing the standard PLCA-R modeled on the conceptual construct of PLCs developed by Hord (1997) as refined by Hipp and Huffman (2010). Data analyses were done using descriptive statistics and analysis of variance tests. The findings of the study are that the attributes under the five dimensions of TQCs are mostly at the initiating stage of development in the six public high schools, the subject of the research. Physical structures—important in creating a culture of collaboration and teamwork— exist in varying degrees, as do collaborative teams. However, the study found that there is an implementation gap between the current practices of TQCs in the public high schools and the kind of collaborative work envisioned in principle and in practice by the Department of Education.